INFLUENCE OF IMPLEMENTATION ARGUMENT-DRIVEN INQUIRY MODEL TO JUNIOR HIGH SCHOOL STUDENTS’ CRITICAL THINKING SKILLS BASED ON DIFFERENCE OF ACADEMIC ABILITY - Hayatun Nufus; Undang Rosidin; Kartini Herlina; Neni Hasnunidah (Jurnal Pendidikan Fisika, 2018)
Critical thinking skills are fundamental skills in 21st century learning. Based on preliminary research in 25 junior high schools in Bandar Lampung, physics teaching and learning has not been maximized in empowering students’ critical thinking skills. This research aims to determine the effect of the implementation of Argument Driven Inquiry learning model to the critical thinking skills of students based on academic ability. This research uses Quasi Experiment method with Pretest Posttest Non Equivalent Control Group Design. The data collected through critical thinking instrument test before and after learning with Argument-Driven Inquiry model. The data were analyzed using Independent Sample T-Test to determine difference after learning through Argument Driven Inquiry model. The results showed that (1) there is effect of implementation Argument Driven Inquiry learning model to critical thinking skill of high academic student shown by sig value. 0,021 (2) there is effect of implementation Argument Driven Inquiry learning model to critical thinking skill of low academic student shown by sig value. at 0.003 at 95% confidence level. We conclude that the implementation of Argument Driven Inquiry model effective to improve the critical thinking skill of students with high and low academic ability